Empowering Women For Chronic Diseases Prevention: A Community-Based Health Initiative at Pos PAUD Mawar Tlogomas Malang - Devi, Hilda Mazarina; Putri, Ronasari Mahaji; Maemunah, Neni; Rosdiana, Yanti; Dewi, Novita (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2026)
The escalating risk of chronic diseases such as Diabetes Mellitus, Gout, and Hypertension among women is driven by several factors including a lack of nutritional literacy, a sedentary lifestyle, and inadequate access to early routine health screenings. A significant portion of this demographic remains unaware that chronic diseases are preventable through behavioral modifications starting in the productive age range (20-39 years). This community service activity was designed as a promotive and preventive effort using an educational approach. The main activities included health education on the risk factors, symptoms, and prevention of Diabetes Mellitus, Gout, and Hypertension through the CERDIK framework, as well as basic health screening such as blood pressure measurement, random blood glucose, and uric acid levels. Conducted on May 21st 2025, the program engaged 19 parents and 6 teachers from the Mawar Tlogomas Early Childhood Center (Pos PAUD) Knowledge levels were assessed using standardized instrument, and health metrics were recorded during the post-test phase. Results indicated that participants’ knowledge reached good category (92%; N=23). Early detection revealed that several participants had elevated levels of blood glucose (12%; N=3), pre-hypertension (72%; N=18), and elevated uric acid level (20%; N=5); they were subsequently advised to seek further examination at health facilities for further clinical evaluation. Participant expressed high enthusiasm and voiced a need for follow-up programs, particularly periodic screenings and training on local-based healthy food processing.